The Challenges of Fighting Crime in the Current Geopolitical Environment - NURTAYEV, Ramazan Tuyakovich; NURTAYEV, Yerden Ramazanovich; KANATOV, Almas Kanatovich; KOZHANTAYEVA, Zhaukhar Kenesbaevna; KERIMKULOV, Adil Temirovich; SIMONENKO, Semen Sergeevich; MUSALIMOV, Isatay Temirzhanovich (Journal of Advanced Research in Law and Economics; Vol 8 No 1 (2017): JARLE Volume VIII Issue 1 (23) Spring 2017, 2017)
The present article considers some aspects of intensifying the fight against crime under the prevailing geopolitical conditions. A threat of both international and common crime spreading on a planetary scale indicates a further increase in the criminological tension in the large part of our planet. This generates an objective need for a theoretical reconsideration of the phenomenon of crime in the current geopolitical environment. As a result of the rethinking of crime trends in the current context, scientific experts put forward disappointing conclusions. One of these conclusions is that a further galloping increase in crime may ultimately be transformed into a real potential threat to the normal existence of the entire human community. With regard to the studies on the specificity and peculiarities of quantitative and qualitative common crime types, representing an increased threat to the interests of mankind, scientists formulated a number of conceptual provisions and recommendations on increasing the efficiency of the fight against crime in the current geopolitical environment.